Revisiting Fintech Adoption in Rural Indonesia: A Contextual Model of Opportunity, Infrastructure, and Risk Attenuation - Isnan Hari Mardika; Rizky Maulana Pribadi; Tri Budi Astuti; Junarti Junarti (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study examines fintech adoption in rural Indonesia by integrating perceptions of fintech opportunities and risks, and infrastructure readiness, into a contextual adoption model. Using a quantitative explanatory design, data were collected through purposive sampling from 122 respondents representing 95 rural villages and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that fintech opportunity perception and infrastructure readiness significantly promote fintech adoption, whereas fintech risk perception has no significant effect. These results indicate that rural users prioritize financial accessibility and practical benefits over perceived risks when digital financial services become a necessity. The study introduces the concept of context-dependent risk attenuation, positing that perceived risk exerts a weaker influence in financially underserved rural settings. The findings extend TAM and UTAUT by emphasizing contextual determinants of technology adoption and provide practical insights for strengthening rural digital infrastructure, financial literacy, and financial inclusion